Pengembangan Pengembangan Multimedia Interaktif Mata Kuliah Multimedia Pembelajaran Di Prodi Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Makassar - Irfan; Febriati, Farida; Mawarni, Sella; Hakim, Abdul (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2024)
The aim of this research is to measure the need for interactive multimedia, design interactive multimedia and measure the validity and practicality of interactive multimedia in the Learning Multimedia course in the Educational Technology Study Program, Faculty of Education, Makassar State University. The approach used in this research is Research and Development (R&D) development with the development model used, namely ADDIE (analysis, design, development, implementation, evaluation). The data sources in this research were 36 students, 1 course lecturer and 2 validators consisting of material/content validators and media validators. The data collection technique is in the form of a questionnaire. The data analysis technique uses qualitative descriptive analysis and quantitative descriptive analysis in the form of needs identification questionnaires, material/content validation questionnaires, media validation questionnaires, small group trial questionnaires, large group trial questionnaires, and course teacher response questionnaires. The research results show that the results obtained from identifying the level of student needs are at the required qualifications. The results obtained from material/content expert validation are in very valid qualifications and media expert validation is in very valid qualifications. To test the level of product practicality, small group trials, large group trials and lecturer responses were carried out. From these three trials, very good qualification results were obtained